Dois documentos, duas histórias e a mesma dor: edição filológica e estudo cognitivo do estupro e do corpo feminino violentado em dois crimes de estupro (1936 e 1941-1942) - Silva, Daianna Quelle da Silva Santos da (2023)
We know that handwritten documents reveal aspects of language, culture, history and memory. Thus, from the moment the philologist has access to such documents, it is possible to remove from ostracism stories that delineate/represent a people and/or a group of peoples. In this thesis, we intend to study two crimes of rape, namely: a Rape Summary, drawn up in 1936, from Santa Bárbara-BA, and a Police Inquiry of rape, drawn up in 1941-1942, from Feira de Santana - BA, to from Philology and Cognitive Linguistics. Thus, aiming to preserve the documents, carefully transcribing the stories respecting the intrinsic and extrinsic aspects of the documents, we opted, within the philological field, to carry out semi-diplomatic editing in the corpus ¬– based on the criteria established in NEMa –Núcleo de Estudos do Manuscrito and Queiroz (2007). When editing the corpus, it was essential to establish dialogues with historical contexts, with some literary texts that deal with rape crimes, such as three stories, Diná, Concubine and Tamar, contained in the Bible (2014), and the short story How many sons Does Natalina have? by Evaristo (2019), and data from our days - the rape case of Mariana Ferrer. These approximations were possible mainly because we adopted the concept of text brought by McKenzie (2005) - text as marked by history, by the author and, also, open, interdisciplinary. Thus, the victims found in the corpus were seen as people without social prestige (they were poor, judging by the statements contained in the corpus) and their situation worsened after the crime, as they were considered without honor, that is, they were revictimized by society. Thus, through the discussions brought by Lose et al (2018), Souza (2014), Sacramento; Santos (2017), Warren (2003) and Ximenes (2020), it was possible to understand that this philological study is a political, visionary, empowering act and also aims to reduce women's vulnerabilities. On this path, the historical, social and cultural aspects, present in the crimes of rape, were woven through the reading of some historians, such as Del Priore (2011), Vigarello (1998), Perrot (2003, 2018) just to mention some. Thus, the female body is punctuated at all times as an object, possession, which represents, in this context, the oppressive and hegemonic character of male power in social relations; female subalternity based on gender hierarchy and the invisibility of violence against women. Based on semantic-cognitive studies, we sought to understand how the violated female body was conceptualized in the corpus. For this endeavor, it was necessary to deal with the Theory of Metaphor and Metonymy, as well as the Theory of Idealized Cognitive Models, the Theory of Image Schemas, Semantics of Frames. Then, we cataloged and analyzed the metaphorical and metonymic expressions in order to elucidate the conceptualizations about the violated female body. Thus, we first structured the conceptualizations of sexual crimes, which were correlated to eight domains, namely: JUSTICE domain, MORALITY domain, VIOLENCE domain, POSSESSION domain, FLORA domain, SEX domain, WAR domain and PURITY domain. Within the domains, we tried to explain the conceptual structure, through the image schemes, bringing the contexts extracted from the corpus and the analyzes that were carried out on the identified metaphors and metonymies. Then, we organized a section on female bodies in sexual violence, in which two metaphors were salutary for the analyses, they are: THE VICTIM'S BODY IS A RECIPIENT and THE VICTIM'S BODY IS THE OBJECT. For the theoretical contribution in the field of Cognitive Linguistics, we used the postulates of Lakoff and Johnson (1980; 1999), in addition to Feltes (2007), Ferrari (2011), Fillmore (1982), Almeida (2021, 2020, 2018, 2016) . And to mirror the analysis of the corpus, we adopted the models of Araújo (2021), Moreira (2015) and Santana (2019), with adaptations.